Stres kerja pada pegawai: Adakah peranan makna kerja? - Hikmah Husniyah Farhanindya; Eko April Ariyanto; Muhammad Fadhlur Rohman Fadhil Athaya Noor Nabila (INNER: Journal of Psychological Research, 2023)
This study aims to examine the existence of a correlation between the meaning of work with work stress on employees. Method of this research is to use quantitative methods. The type of research used is correlational. Subjects of this study were 62 employees. The scale of the meaning of work in this study was compiled referring to the opinion put forward by Steger, et al (2012). While the work stress scale in this study was compiled based on the opinion of Robins (2006). The research data was tested using the product moment parametric technique. The hypothesis put forward in this study is accepted, with the test results showing that there is a very significant negative relationship between the meaning of work and work stress. This means that this research shows that the higher the work meaning score, the lower the work stress score. Conversely, the lower the work meaning score, the higher the work stress score on employees. This shows that the importance of increasing the positive meaning of work for employees can minimize work stress on employees.